Long Noncoding RNA KLF3-AS1 Acts as an Endogenous RNA of miR-223 to Attenuate Gastric Cancer Progression and Chemoresistance - Jiang, Houxiang; Hu, KaiFeng; Xia, Yabing; Liang, Linhu; Zhu, Xiaoli (Frontiers in Oncology, 2021)
Gastric cancer is a deadly disease, and the low rate of early diagnosis and chemoresistance largely contributed to the poor prognosis of gastric cancer. LncRNAs have been extensively reported for their roles in regulating cancer progression. In this study, we found that KLF3-AS1 was down-regulated in gastric cancer cells. Overexpression of KLF3-AS1 repressed gastric cancer cell proliferation, growth. In addition, KLF3-AS1 overexpression also exerted inhibitory effects on the gastric cancer cell invasion, migration and EMT, but promoted chemosensitivity of gastric cancer cells to cisplatin. The mechanistic studies showed that KLF3-AS1 could act as the “sponge” for miR-223 and to repress miR-223 expression in gastric cancer cells. Overexpression of miR-223 reversed the inhibitory effects of KLF3-AS1 overexpression on gastric cancer cell proliferation, invasion, migration and EMT, and attenuated the enhanced effects of KLF3-AS1 overexpression on gastric cancer cell chemosensitivity to cisplatin. The in vivo studies showed that KLF3-AS1 overexpression suppressed the tumor growth of SGC-7901 in the nude mice. In conclusion, our results for the first time demonstrated that KLF3-AS1 was down-regulated in gastric cancer cells and repressed gastric cancer cell proliferation, invasion, migration and EMT, and enhanced chemosensitivity to cisplatin. Further mechanistic results indicated that KLF3-AS1 exerted its biological function in gastric cancer cells by inhibiting miR-223 expression. Future studies are still required to decipher the detailed molecular mechanisms of KLF3-AS1 in gastric cancer.